The Application and Limitation of Universal Chloroplast Markers in Discriminating East Asian Evergreen Oaks - Yan, Mengxiao; Xiong, Yanshi; Liu, Ruibin; Deng, Min; Song, Jiaojiao (Frontiers in Plant Science, 2018)
The East Asian subtropics mostly occupied by evergreen broad-leaved forests (EBLFs), is one of the global diversity centers for evergreen oaks. Evergreen oaks are keystone canopy trees in EBLFs with important ecosystem function and crucial significance for regional biodiversity conservation. However, the species composition and diversity of Asian evergreen oaks are poorly understood. Here, we test whether the four chloroplast markers atpI-atpH, matK, psbA-trnH and ycf1, can discriminate the two evergreen oak sections in Asia - Cyclobalanopsis and Ilex. 272 individuals representing 57 species were scanned and 17 species from other oaks sections were included for phylogenetic reconstruction. The genetic diversity of the Quercus sections was also compared. Overall, we found that universal chloroplast DNA barcoding markers could resolve two clades in Quercus, i.e., subgenus Cerris (Old World Clade) and subgenus Quercus (New World Clade). The chloroplast markers distinguished the main sections, with few exceptions. Each cpDNA region showed no barcoding gap and none of them provided good resolution at the species level. The best species resolution (27.78%) was obtained when three or four markers were combined and analyzed using BLAST. The high conservation of the chloroplast DNA and complicated evolutionary patterns, due to incomplete lineage sorting, interspecific hybridization and introgressions may hinder the ability of cpDNA markers to discriminate different species. When comparing diversification pattern across Quercus sections (Cyclobalanopsis, Ilex, Cerris, Quercus and Protobalanus), we found that section Ilex was the most genetically diverse, and section Cyclobalanopsis was lower genetically diverse. This diversification pattern may have resulted from the interplay of the Eurasia Cenozoic tectonic movements, climate changes and different niches of their ancestral lineages.